2009
DOI: 10.1258/rsmmsl.49.3.191
|View full text |Cite
|
Sign up to set email alerts
|

Organ donation in France: legislation, epidemiology and ethical comments

Abstract: The Bioethics Laws revised in 2004 have defined rules concerning organ donation and transplantation. They have also permitted the creation of the French Biomedicine Agency which guarantees the right of enforcement. In France there are three situations in which organs may be harvested: from cadaveric donors, from living donors and, since 2005, from non heart beating donors. Organ harvesting from cadaveric donors is permissible if the deceased did not make known his refusal during his lifetime (this may be recor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…In France, brain death is a clinical and legal diagnosis, as previously described [ 21 23 ]. In France, care can be continued pending brain death determination, but when a decision of withdrawal of life-sustaining therapy is made, patients are no longer suitable for a process of donation after brain death.…”
Section: Methodsmentioning
confidence: 99%
“…In France, brain death is a clinical and legal diagnosis, as previously described [ 21 23 ]. In France, care can be continued pending brain death determination, but when a decision of withdrawal of life-sustaining therapy is made, patients are no longer suitable for a process of donation after brain death.…”
Section: Methodsmentioning
confidence: 99%
“…As recommended, the clinical diagnosis of BD was made in the absence of confounding factors (e.g., residual sedation) [16]. Ancillary tests (e.g., computed tomography angiograph or electroencephalogram) were used to confirm BD when the apnea test could not be performed and/or, according to French law, when organ donation was considered [17].…”
Section: Methodsmentioning
confidence: 99%
“…Organ harvesting from a cadaveric individual is authorized if the individual did not make known his refusal during his or her lifetime. However, the consent of the family is always necessary to collect organs from a cadaveric individual (Jousset, Gaudin, Mauillon, Penneau, & Rougé-Maillart, 2009). Abadie and Gay (2004) reported that about 30% of the families that are approached by the medical team to request donation refuse it.…”
Section: Religious Primingmentioning
confidence: 99%